Principles of organization and realization of legal examination of legal acts - Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to research of basic principles of organization and realization of legal examinationin the process of lawmaking activity of the state. The author in this investigation determines basic principlesof legal examination of legal acts and their realization in lawmaking activity.